Farinhas de banana verde e sorgo com elevados teores de amido resistente: obtenção, caracterização e uso na produção de biscoitos tipo cookie avaliados sensorialmente - Natalia de Carvalho Teixeira (2016)
Cookies were produced using different proportions of hybrid sorghum flour BR 305 and green banana flour with high resistant starch (RS) content and subjected to sensory evaluation. Initially the RS content in sorghum were studied in order to find genotypes with high levels of this component as well as the influence of dry and moist heat in its retention. Among the 49 studied sorghum genotypes, the SC59 presented 65.66 g / 100 g of RS, and was considered a good RS source, with the BR 305 Hybrid (52.26 g / 100 g of RS). For both genotypes, the moist heat led to a drastic loss of RS after boiling the grain and the flour, while the dry heat resulted in a maximum loss of 15% of RS and, therefore, better thermal processing option for sorghum flour. The conditions of time and temperature most suitable for the green banana flour production with high RS content were also evaluated. In general, green banana flour produced using the shorter time (4 hours) and the lowest temperature (40 °C) showed the highest level of RS (77.89 g / 100 g), and these conditions resulted in a green banana flour with RS content significantly (p < 0.05) higher than in in nature green bananas. The flour prepared under these conditions presented clear color, according to the evaluation of optical parameters, which allows its incorporation into various types of food, while the fiber content and phenolic compounds were significantly (p < 0.05) lower than in in nature green banana. The cookie made with 100% of this green banana flour presented RS levels significantly (p <0.05) higher than the other products studied. This cookie assigned evaluated by biscuit consumers, presented better acceptance means, and was characterized as having a clear color. None of the products presented acceptance means the rejection area of hedonic scale used. Moreover, none of the experimental formulations had significantly lower mean acceptance than the product made with wheat flour, demonstrating the potential use of green banana flour and sorghum flour in the cookie development.